Clinical and microbiological characteristics and prognosis of invasive infection caused by Klebsiella pneumoniae in the community - Hongkui Sun; Hanlin Zhang; Wenqing Lai; Li Lei; Jianwei Li; Miaolian Chen; Haijun Li; Zhanyuan Zhao (Annals of Medicine)
Background The incidence of invasive infection of Klebsiella pneumoniae (Kp) in the community is increasing every year, and the high disability and mortality rates associated with them pose great challenges in clinical practice. This study aimed to explore the clinical and microbiological characteristics of Kp invasive infection in the community.Method This study investigated the data of 291 patients with Kp infection in the community in three hospitals (Zhongshan City, Guangdong Province) from January 2020 to August 2023. The risk factors for invasive infection and death due to Kp infection were determined through multivariate logistic regression models and Cox models.Result The mortality rate of community-acquired Klebsiella pneumoniae (cKp) invasive infections markedly exceeded that for non-invasive infections (47.6% vs 25.9%) (p = 0.001). Multivariate logistic regression analysis identified high viscosity type (OR:2.26, p = 0.031) and shock (OR:3.42, p = 0.001) as significant risk factors for invasive infection. Among patients who succumbed to invasive infections, multivariate Cox regression analysis revealed that elevated CK-MB (OR: 1.01, p = 0.040), increased IL-6 levels (OR: 1.00, p = 0.023), and high SOFA scores (OR: 1.16, p = 0.017) were linked to increased mortality risk. This study found that co-infection of the liver, lungs, and bloodstream was most prevalent in invasive infections. Notably, co-infection involving the lungs, bloodstream, and brain was associated with the highest mortality rate (100%, 6/6). No significant differences were found between patients with or without invasive infections, as well as between surviving and non-surviving patients (all p ≥ 0.05).Conclusion Patients with cKp invasive infections exhibit more severe inflammatory responses and a poorer prognosis, necessitating vigilant attention from clinicians. The treatment of cKp invasive infections remains inconclusive between "heavy-handed strikes" and "sensitivity is sufficient". Focusing solely on the liver and lungs while neglecting infection sites outside of these organs can lead to catastrophic results, which should be avoided during treatment.